Importance of the mesoscale in the decadal changes observed in the northern Canary upwelling system - Relvas, Paulo (2018)
Analysis of sea surface temperature (SST) time series since 1960 from existing data bases shows a generalized warming trend in the northern Canary upwelling system. The field of the satellite-derived SST trends off Western Iberia was built at the pixel scale (4 x 4 km) for the period 1985-2008, revealing significant spatial differences in the warming rates. Weaker warming trends fit to the known upwelling pattern off the southern part of the Western Iberia, pointing out the intensification of this feature since 1985, particularly during the peak summer months. A more regular behavior is found further north suggesting significant decadal changes in the mesoscale patterns of the northern Canary upwelling system. Citation: Relvas, P., J. Luis, and A. M. P. Santos (2009), Importance of the mesoscale in the decadal changes observed in the northern Canary upwelling system, Geophys. Res. Lett., 36, L22601, doi:10.1029/2009GL040504.